PFL: readability factors in literary retextualization - Machado, Ana Maria; Fernandes, Anabela (BELT - Brazilian English Language Teaching Journal, 2019)
The “Literature in Portuguese Foreign Language Teaching” project aims to introduce extensive reading of simplified versions of literary texts (19th-21th century) in the first stage (Beginners Level) of Portuguese as a Foreign Language courses. Using a literature-based approach to language learning as a potential source of cultural input enhances learners’ creativity. During the project’s first phase, we tested a simplified sample of the novel O Senhor Ventura (1943/1985), from Miguel Torga, in the context of formal learning, in order to assess the suitability of the text for this particular language proficiency level. After collecting data and considering students’ needs, we have selected notations and pictures and we have built a questionnaire that will contribute to the improvement of their reading and comprehension skills.